In-situ X-ray tomographic imaging and controlled steering of microcracks in 3D nanopatterned structures - Kristina Kutukova; Jürgen Gluch; Matthias Kraatz; André Clausner; Ehrenfried Zschech (Materials & Design, 2022)
An experimental approach to control the fracture behavior of 3D nanopatterned structures in real time and to describe the microcrack propagation in solids quantitatively is presented. The three-dimensional details of the complicated failure mechanism are unveiled with high resolution using a method that integrates a micro-scale fracture mechanics test into a nano X-ray computed tomography system, to allow in-situ 3D imaging of the kinetics of damage mechanisms in integrated circuits. With the unique combination of a miniaturized micro-mechanical experiment and high-resolution X-ray imaging, the critical energy release rate at the crack tip of materials is determined quantitatively in sub-100 nm dimension, which allows to reveal scale-dependent mechanical properties. The ability of controlled microcrack steering in engineered materials and structures into regions with high fracture toughness is demonstrated. This unique characterization capability promises broad applications for design and manufacturing of robust microchips in future technology nodes, and it is applicable to the study of a broad variety of 3D nanostructured material systems.